(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the clinical characteristics and investigate several factors associated with acne vulgaris. Subjects and methods: A cross-sectional descriptive study was conducted on 182 outpatients diagnosed with acne vulgaris at Thai Nguyen University of Medicine and Pharmacy Hospital. Results: Females accounted for 59.3%, males for 40.7%; the incidence before age 20 was 90.1%; the clinical form of occult acne is the most common (62.1%), lesions were most frequently distributed on the forehead (76.9%), mild severity accounted for 61.3%, moderate severity for 35.9%, and severe severity for 2.8%. Conclusion: Acne vulgaris was more common in females than in males, with most cases occurring before the age of 20. The most frequent primary lesions were closed comedones, open comedones, and whiteheads. Lesions were predominantly distributed on the face, with mild and moderate severity accounting for the majority of cases. A high-fat diet, late-night habits, and family history were factors significantly associated with the severity of acne vulgaris. Conclusion: The most common clinical form of common acne is the occult acne, with most patients experiencing mild to moderate symptoms.